Finite State Predictive Current and Common Mode Voltage Control of a Seven-phase Voltage Source Inverter - Atif Iqbal; Shaikh Moinoddine; Khaliqur Rahman (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
The paper elaborate finite set model based predictive current control of a seven-phase voltage source inverter. The current control is carried out considering a finite set of control actions. The space vector model of a seven-phase voltage source inverter (VSI) yields 27 = 128 space voltage vectors, with 126 active and two zero vectors. The control method described in this paper discard some switching states from the whole set and employs reduced number of switching states to track the commanded current. Three sets of space vectors are used for switching actuation, in one case only 15 vectors are used (14 active and one zero), in second case 29 vectors are used (28 active and one zero) and finally 43 vectors (42 active and one zero) are employed. Optimal algorithm is employed to find the vector which minimizes the chosen cost function. The effect of selecting the cost function, the number of space vectors and the sampling time is investigated and reported. The developed technique is tested for RL load using simulation and experimental approaches.